2013
DOI: 10.1001/jamapsychiatry.2013.684
|View full text |Cite
|
Sign up to set email alerts
|

Selected Pregnancy and Delivery Outcomes After Exposure to Antidepressant Medication

Abstract: Importance: Untreated depression during pregnancy has been associated with increased morbidity and mortality for both mother and child and, as such, optimal treatment strategies are required for this population. Context: There are conflicting data regarding potential risks of prenatal antidepressant treatment. Objective: To determine whether prenatal antidepressant exposure is associated with risk for selected adverse pregnancy or delivery outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(170 citation statements)
references
References 92 publications
(101 reference statements)
11
155
0
4
Order By: Relevance
“…(53) A meta-analysis of 13 studies, primarily in LMICs, concluded that the most effective interventions for mothers with depression included infant massage and support groups Antidepressants for treatment of antenatal depression, on the other hand, have been associated with small but significant increases in preterm birth and reductions in birth weight. (59,60) Persistence of depression (into the postnatal period and beyond) seems to be of particular importance in relation to cognitive development, including achievement of developmental milestones, and language development. (56) Recent trials from Bangladesh(61) and Uganda (62) suggest that group-based parenting programmes can improve maternal mental health in community settings and young children's cognitive and receptive language scores.…”
Section: Maternal Stress Depression and Mental Disordersmentioning
confidence: 99%
“…(53) A meta-analysis of 13 studies, primarily in LMICs, concluded that the most effective interventions for mothers with depression included infant massage and support groups Antidepressants for treatment of antenatal depression, on the other hand, have been associated with small but significant increases in preterm birth and reductions in birth weight. (59,60) Persistence of depression (into the postnatal period and beyond) seems to be of particular importance in relation to cognitive development, including achievement of developmental milestones, and language development. (56) Recent trials from Bangladesh(61) and Uganda (62) suggest that group-based parenting programmes can improve maternal mental health in community settings and young children's cognitive and receptive language scores.…”
Section: Maternal Stress Depression and Mental Disordersmentioning
confidence: 99%
“…57,58 There have been small but significant associations between the use of SSRI/SNRIs and spontaneous abortions, as well as shorter gestational age, preterm delivery, and lower APGAR scores in neonates. [59][60][61] Additionally, an increased risk of persistent pulmonary hypertension of the newborn has been associated with third trimester SSRI/SNRI exposure; 62 the absolute risk, however, is small-3 to 4 cases per thousand. 63 Third trimester exposure has been related to neonatal withdrawal symptoms, such as jitteriness, irritability, tremulousness, difficulty feeding, difficulty sleeping, hypertonia, and other adverse symptoms such as seizures.…”
Section: Antidepressantsmentioning
confidence: 99%
“…We selected 2 specific antidepressants (fluoxetine and paroxetine) for a separate analysis of their effect on malformations where sufficient data were available, as more information was available for them compared to others. All analyses were conducted with Stata statistical software, version 10.1 (StataCorp LP) 29 and similar to our other work in Ross et al 30 …”
Section: Statistical Analysesmentioning
confidence: 99%